Invasive mole presenting as abnormal uterine bleeding: a case report and review of literature - Nandan, Neetha; Shetty, Vijith; Lekkala, Rachana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Invasive mole is a type of gestational trophoblastic neoplasia (GTN). It usually occurs after a molar or non-molar pregnancy. Here we would like to present a 47-year-old nulligravida lady who does not give any history of antecedent pregnancy. She had symptoms of abnormal uterine bleeding (AUB) and came to the causality with heavy flow. Beta hCG was very high and MRI showed uterine tumor. She underwent total abdominal hysterectomy with bilateral salpingoopherectomy which showed invasive mole FIGO stage II. Her WHO prognostic score was 9 and hence she received EMA-CO regimen of chemotherapy. GTN can present in different ways, even without a history of previous pregnancy. In such situations a high level of suspicion and a simple Beta hCG level can clinch the diagnosis.